PENGARUH JENIS PELARUT DAN WAKTU MASERASI TERHADAP EKSTRAK DAUN JARAK PAGAR (Jatropha cur-cas Linn) DALAM MENGHAMBAT Escherichia coli DAN Staphylococcus aureus - Khofifah, Arfira; Antara, Nyoman Semadi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): JuniDO - 10.24843/JRMA.2022.v10.i02.p02, 2022)
E. coli bacteria and S. aureus bacteria that can cause disease or infection. Infection is a disease caused by pathogenic microorganisms in the body. Most of the causes of bacteria or microorganisms in the body are antibiotic resistance. An alternative that can be done for antibiotic resistance is by developing antibacterial drugs. Jatropha leaf extract can be developed as an anti-bacterial. This study used a factorial randomized block design (RBD) with two factors. The first factor is the type of solvent which consists of n -hexane, methanol and Ethyl Acetate. The second factor is the maceration time which consists of 24, 36, and 48 hours. The data were analyzed by analysis of variation and if the treatment had an effect, it was continued with the Tukey test. The results showed that the type of solvent treatment and maceration time had a very significant effect on yield, anti-bacterial and minimum inhibitory concentration (MIC). In the test bacteria E. coli , the ethyl acetate solvent with a maceration time of 36 hours was the best treatment for antibacterial activity of 11.50±2.83 mm (weak), in the test bacteria S. aureus , the methanol solvent with a maceration time of 36 hours, was the best treatment for antibacterial activity bacteria 19.70±0.35 (strong).